Respuestas

2012-12-08T05:47:30+01:00

a) -6-(x-1) = 7-6        
    -6 -x +1 = 1
        -x -5 = 1
           -x  = 1+5 
           -x  = 6
            x  = 6/(-1)
            x  = -6
b) 12 + 3x -32 = -17 -(-x-5)
     -20 + 3x    = -17 +x +5
          3x -x    = -17 + 5 + 20
               2x   = 8
                 x  = 8/2
                 x = 4
c) 2x - 12-(13-1) = 15-(-x+2)
     2x -12 -13 +1 = 15 +x -2
          2x - x       = 15 -2 +12 +13 -1
                x        =  27 
d)19 -(-x+1) = 2x -32
    19 +x -1   = 2x -32
       18 + x   = 2x -32
          x - 2x = -32 -18
           -x     = -50
              x   = -50/(-1)
              x   = 50